Correction to: Feminist Storytelling and the Problem of White Feminism (Literature and theology, 2023)
This is a correction to: Amanda Griffin, Feminist Storytelling and the Problem of White Feminism, Literature and Theology, Volume 35, Issue 2, June 2021, P